MANAGEMENT OF ONION PEEL KITCHEN WASTE RED IS A GROWTH REGULATING SUBSTANCE IN GAMPONG LAMCEU, KUTA BARO DISTRICT, ACEH BESAR REGENCY: PENGELOLAAN LIMBAH DAPUR KULIT BAWANG MERAH MENJADI ZAT PENGATUR TUMBUH DI GAMPONG LAMCEU KECAMATAN KUTA BARO KABUPATEN ACEH BESAR - Mulyanti; Maghfirah; Sri Agustina; Reza Salima; Ayuliza (PT. ROCE WISDOM ACEH, 2024)
Gampong Lamcceu is one of the villages located in Kuta Baro District, Aceh Besar Regency. Administratively, Lamceu gampong has 3 (three hamlets), namely Lamceu Hamlet, Lamtuha Hamlet, Lam Hamlet. Residents of Lamceu Village generally work in the agricultural sector either as farmers, breeders, gardeners and only a small number work outside the agricultural sector such as Civil Servants. , traders and teaching staff (non-PNS teachers or lecturers). The people of Lamceu village generally carry out plant cultivation activities, both plantation crops and agriculture, which is their main occupation. The survey results show that one of the problems faced by the community is the low level of public knowledge about kitchen waste management. The solution to the problems faced by the community is by providing knowledge on how to process kitchen waste into plant growth regulators by utilizing the potential of natural resources in the village to improve community welfare. The people of Lamceu Village, especially the PKK women, are very enthusiastic about participating in this Community Service Activity. The result of this Community Service Activity is that the community understands the process of making red onion skin kitchen waste into a growth regulator